Organocatalytic Atroposelective Reactions of Alkynes - Zhang, Zhi-Xin; Hu, Tian-Qi; Ye, Long-Wu; Zhou, Bo (Synthesis, 2024)
The atroposelective transformation of alkynes is an efficient protocol for the assembly of axially chiral compounds. Benefitting from the rapid development of chiral organocatalysts, the organocatalytic atroposelective reactions of alkynes have been extensively studied over the past decades. An array of chiral catalysts, including chiral Brønsted acid catalysts, secondary amine catalysts, N-heterocyclic carbene (NHC) catalysts, thiourea catalysts and N-squaramide catalysts, are employed in enantioselective reactions of different alkynes. This short review summarizes the recent advances on organocatalytic atroposelective reactions of alkynes according to the type of alkyne substrate. The reaction mechanisms, modes of enantiocontrol, product diversity and applications are highlighted.1 Introduction2 Electron-Rich Aryl Alkynes3 Electron-Deficient Aryl Alkynes4 Other Types of Alkynes5 Conclusion and Outlook
Keywords: organocatalysis; enantioselectivity; alkynes; axially chiral compounds; reaction mechanism